The effect of work motivation and work environment on the performance of Mitra10 Karawang employees - Riski Eko Ardianto; Rensi Suryanti (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of work motivation and work environment on the performance of Mitra10 Karawang employees. So the objectives to be achieved in this research are, to find out how much work motivation and work environment affect the performance of Mitra10 Karawang employees, to find out how much motivation work affects the performance of Mitra10 Karawang employees, to find out how much the work environment affects the performance of Mitra10 Karawang employees, which independent variable has the most dominant effect on employee performance. The research method used is a quantitative method through an associative approach. The research location is Mitra10 Karawang, Teluk Jambe, West Karawang. The sample selection method in this study is a saturated sample (census). The data analysis technique used classical assumption test, multiple linear regression test, f test and t test. The results of this study indicate that work motivation and work environment have a simultaneous effect on employee performance, partially work motivation has a positive and significant effect on employee performance, work environment has a positive and significant effect on employee performance, dominantly work motivation variable affects employee performance. The implication of this research is that there are cleanliness observers and workspace observers so that the tasks given by employees are done well and it is hoped that work motivation will increase the passion and enthusiasm of employees in a company.